2004
DOI: 10.1002/dev.20029
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical response to stress in fasted and unfasted artificially reared 12‐day‐old rat pups

Abstract: Recent studies have compared artificially reared (AR) rats with dam-reared rats on behavioral outcomes but, despite the fact that they are deprived of their mothers during the stress hyporesponsive period (SHRP), little is known about the effects of AR on the development of the stress response. In this study, the corticosterone (CORT) response to a stressor (saline injection ip) on postnatal Day 12 was assessed in rat pups that had been either dam-reared (DR) or artificially reared since Day 5. In the precedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
2
13
1
Order By: Relevance
“…They also tended to avoid the center of the open field, suggesting increased emotionality and fearfulness in a novel setting (Gonzalez et al, 2001;Kaneko et al, 1996). Conversely, infant (Ward, Xing, Carnide, Slivchak, & Wainwright, 2004) and adult (Kelly, Mahoney, Randich, & West, 1991) AR rats did not differ in stressinduced corticosterone levels compared to MR rats, although some differences in stress responsiveness were evident under conditions of food deprivation (Ward et al, 2004) or exposure to ethanol (Kelly et al, 1991).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…They also tended to avoid the center of the open field, suggesting increased emotionality and fearfulness in a novel setting (Gonzalez et al, 2001;Kaneko et al, 1996). Conversely, infant (Ward, Xing, Carnide, Slivchak, & Wainwright, 2004) and adult (Kelly, Mahoney, Randich, & West, 1991) AR rats did not differ in stressinduced corticosterone levels compared to MR rats, although some differences in stress responsiveness were evident under conditions of food deprivation (Ward et al, 2004) or exposure to ethanol (Kelly et al, 1991).…”
Section: Introductionmentioning
confidence: 75%
“…There is little known to date about the stress responsiveness of AR rats. The only reports thus far indicate that infant (Ward et al, 2004) and adult (Kelly et al, 1991) AR rats did not differ in stress-induced corticosterone levels from MR controls, unless they were also food deprived for 24 hr, where they showed a lower corticosterone response to an injection stressor compared to similarly deprived MR rats (Ward et al, 2004). These findings are in contrast to reports of increased endocrine stress reactivity shown in adult maternally separated rats (Hsu et al, 2003;Liu et al, 2000;Meaney et al, 2002;Plotsky & Meaney, 1993), suggesting that the AR procedure may not lead to the same HPA axis activation seen in maternal separation.…”
Section: Figurementioning
confidence: 94%
“…Conversely, maternal separation as well as artificial rearing decrease maternal licking and crouching behavior in adulthood; however, only artificial rearing has a robust disruptive effect on juvenile maternal behavior (Gonzalez & Fleming, 2002;Gonzalez, Lovic, Ward, Wainwright, & Fleming, 2001;Lovic et al, 2001;Rees and Fleming, 2001). Whether these effects of artificial rearing on maternal behavior are due to changes in the HPA axis remain unclear, although research has shown that artificial rearing does not affect baseline or stress-induced levels of corticosterone (Burton, Chatterjee, Chatterjee-Chakraborty, Lovic, Grella, Steiner, & Fleming, 2007;Ward, Xing, Carnide, Slivchak, & Developmental Psychobiology Wainwright, 2004). This, along with the present data, suggests that the effects of early preweaning experiences on both juvenile and adult maternal behavior may not be linked to changes in the HPA axis.…”
Section: Discussionmentioning
confidence: 94%
“…By allowing direct control of many of the variables associated with the maternal environment, it provides another model to study the role of early life experience in behavioral development. Previous work in our laboratory suggested differences in HPA axis function between preweaning male AR and maternally reared (MR) rats (17). In addition, male AR rats displayed a greater response to both natural and drug-mediated rewards than male MR rats (18).…”
mentioning
confidence: 77%